2009
DOI: 10.3171/2009.8.focus09140
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical mapping and monitoring during insular tumor surgery

Abstract: Object The treatment of insular tumors is controversial. Surgical treatment is associated with a higher morbidity rate than other therapies. The present work presents a new method in which the descending motor pathways are monitored during surgery for insular tumors. Methods Intraoperative monitoring was performed in a combination of 2 techniques. The motor cortex was stimulated with a transcranial elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 64 publications
0
42
1
5
Order By: Relevance
“…25,52 The reference electrode was placed at Fzp. 10 Identical stimulation parameters as described above for DCS were applied (TOF stimuli, interstimulus interval 4 msec, pulse duration 500 µsec).…”
Section: Standard Mapping Using a Fingerstick Probementioning
confidence: 99%
See 1 more Smart Citation
“…25,52 The reference electrode was placed at Fzp. 10 Identical stimulation parameters as described above for DCS were applied (TOF stimuli, interstimulus interval 4 msec, pulse duration 500 µsec).…”
Section: Standard Mapping Using a Fingerstick Probementioning
confidence: 99%
“…22,25,36,37,39 We recently showed that a safe mapping corridor for mechanical injury of the CST exists between high and low MTs, and that both significant signal changes in motor evoked potential (MEP) monitoring and permanent motor deficits do not occur before very low MTs of < 1-2 mA. 45 We also provided data supporting the hypothesis that the interruptive and punctiform technique of mapping with insufficient spatial and temporal coverage of the surgical site may be a cause of motor deficits despite higher and apparently safe MTs (3-6 mA).…”
mentioning
confidence: 99%
“…A safe window has been described for monopolar high-frequency TOF mapping between 20 mA and 3-5 mA 16,19,25,27,28,47 or even 1-3 mA. 38 An MT within this range excludes mechanical damage of the CST and permanent motor deficit, provided that the measured MT is indeed the lowest in the resection cavity, the surgeon does not continue resection after mapping, and no vascular injury has occurred.…”
Section: How Close To the Cst Can We Safely Resect Tumor Tissue?mentioning
confidence: 99%
“…31,37 An MT-to-distance relationship exists for subcortical monopolar TOF mapping of the CST. 16,19,27 As a rule of thumb, 1 mA of current corresponds to 1 mm remaining distance to the CST. 27,28 We previously demonstrated a safe window between high and low MTs for mechanical injury to the CST and showed that significant signal changes in MEP monitoring and permanent motor deficits do not occur above very low MTs of less than 1-2 mA.…”
mentioning
confidence: 99%
See 1 more Smart Citation